Relationship Marketing sebagai Upaya untuk Mempertahankan Loyalitas Pelanggan: - Farah Chalida Hanoum; Yanti Hasbian Setiawati (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2021)
Relationship marketing establishing, developing and maintaining succesful relational exchanges constitutes a major shift in marketing theory and practice. Relationship marketing refer to all marketing activities directed toward establishing, developing and maintaining succesful relational exchanges.